PEMBENTUKAN KARAKTER QURANI MELALUI PEMBELAJARAN TAFSIR AL-QUR’AN - Ruspandi, Didik (El-Waroqoh : Jurnal Ushuluddin dan Filsafat, 2024)
The Book of Tafsir Al-Munir is a book of interpretations of the Qur'an which contains Qur'anic characters, namely religious characters in terms of faith and piety. Seeing the problems of recent students who have begun to decline in character, researchers are interested in discussing the character that a student or seeker of knowledge must have. This study focuses on the process of learning Al-Qur'an interpretation at Tahfidz Al-Amien Prenduan Sumenep High School, the formation of Qur'anic character through learning Al-Qur'an interpretation, as well as the Supporting and Inhibiting Factors of learning Al-Qur'an interpretation in SMA Tahfidz Al-Amien Prenduan Sumenep. To answer this problem, research was carried out using a qualitative approach with a case study type. The research location is at SMA Tahfidz Al-Amien Prenduan Sumenep, which is located in Pragaan Laok Village, Pragaan District, and Sumenep Regency. The data sources in this study are the principal, the teacher's council and students. Data collection was carried out by interviews, observation and documentation of a number of related sources. Data analysis techniques using descriptive data analysis techniques. The results showed that the process of learning the interpretation of the Qur'an was carried out on a scheduled basis in each class, using the lecture and question and answer method starting with the reading of the verses then continued by the students following the readings, then explaining the position of the verses, then the beauty of the language (Balaghah), followed by interpreting the words, then the suitability of the verse with the previous discussion, then interpreting and explaining, and finally the conclusion. The formation of this Qur'anic character is implemented through instilling religious character points in learning the interpretation of the Qur'an, namely faith and piety according to the vision and mission of Tahfidz Al-Amien High School. with the implementation in accordance with the guidance of the Qur'an, namely Surah Al-Baqarah which contains the signs of people who believe and fear those who believe in the unseen, perform prayers, and spend part of the sustenance that Allah gives to them, those who believe in the Al-Qur'an 'an which was revealed to you by the Prophet Muhammad by reading, memorizing, understanding and practicing, and they believe in the hereafter. Supporting factors in learning the interpretation of the Qur'an consist of: teachers, students, learning resources, and infrastructure. While the inhibiting factors consist of: not being able to read the yellow book.